EFFICIENCY OVER LEARNING: A QUALITATIVE STUDY OF CHATGPT USE AND ACADEMIC INTEGRITY AMONG JUNIOR HIGH SCHOOL STUDENTS IN INDONESIA - Sohibatul Islamiyah; Durrotul Hikmah (English Review: Journal of English Education, 2026)
The increasing use of ChatGPT in secondary education has raised questions about its impact on students’ learning and academic integrity. However, empirical evidence on junior high school students’ perspectives, particularly in the Indonesian context, remains limited. This qualitative descriptive study explores students’ perceived benefits, challenges, and ethical strategies in using ChatGPT for academic writing. The study involved five junior high school students (ages 13–15) from SMP Nurul Jadid, Indonesia, selected through purposive sampling based on their experience using ChatGPT for writing tasks. Data were collected through semi-structured interviews and analyzed using Braun and Clarke’s reflexive thematic analysis. The findings show that students primarily use ChatGPT for efficiency-related purposes, such as quick access to information and task completion, rather than for developing writing skills or critical thinking. Reported challenges were minimal, indicating limited awareness of issues such as AI inaccuracies and overreliance. To address ethical concerns, students developed self-constructed strategies based on selective use and content modification; however, these were found to be insufficient in addressing deeper issues of academic integrity and proper attribution. The study highlights a gap between the pedagogical potential of ChatGPT and students’ actual usage, underscoring the need for explicit instruction and clear guidelines to support responsible and learning-focused AI use in secondary education.